2010
DOI: 10.1088/0957-4484/21/10/105702
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic synergy of graphitic nanoplatelets and multi-walled carbon nanotubes in polyetherimide nanocomposites

Abstract: Hybridizing graphitic nanoplatelets (GNP) with commercially functionalized multi-walled carbon nanotubes (MWCNTs) in a polyetherimide (PEI) composite at a total loading of 0.5 wt% resulted in considerable improvements in electrical conductivity, thermal conductivity and dynamic mechanical properties, compared to solely GNP or solely MWCNT composites at the same total loading. The results reveal a synergistic interaction between the GNPs and MWCNTs based on GNP protection against fragmentation of the MWCNTs dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
91
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(102 citation statements)
references
References 40 publications
8
91
0
3
Order By: Relevance
“…Fan et al [10] noted a decrease of the percolation threshold and a higher electrical conductivity by combining CB with graphite nanoplatelets (GNP). Similar positive effects have been observed in carbon nanotube (CNT)/graphite nanoplatelet hybrids [11][12][13] and CNT/GNP/CB hybrids [14]. Furthermore, by combining CNT with CB or GNP the viscosity of the composite melt has been reported to decrease in comparison to single filler composite melt at the same filler loading [15].…”
Section: Introductionsupporting
confidence: 59%
“…Fan et al [10] noted a decrease of the percolation threshold and a higher electrical conductivity by combining CB with graphite nanoplatelets (GNP). Similar positive effects have been observed in carbon nanotube (CNT)/graphite nanoplatelet hybrids [11][12][13] and CNT/GNP/CB hybrids [14]. Furthermore, by combining CNT with CB or GNP the viscosity of the composite melt has been reported to decrease in comparison to single filler composite melt at the same filler loading [15].…”
Section: Introductionsupporting
confidence: 59%
“…Most of the studies reported in the literature on the use of hybrid filler systems were performed in epoxy resins [19][20][21][22][23][24]. Concerning the electrical percolation threshold, only small effects were found when replacing parts of the nanotubes by other conductive fillers or when additionally adding them.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of examples exist in the literature, entailing different constituents and different mechanical properties, with emphasis on modulus strength and fracture toughness, as presented in a variety of papers. [1][2][3][4][5][6] The re-discovery of carbon nanostructures in the 1990s 7 -and eventually of a host of other nanoparticlesgenerated immediate interest in the prospects of harnessing nanoparticles to ultra-high mechanical property composite materials, termed nanocomposites. It was their nominal mechanical properties, being orders of magnitude higher than those of classical reinforcement fibers, which made nanoparticles attractive as reinforcement constituents, wherein low concentrations would be OPEN ACCESS potentially required to match and surpass properties of classical composites of high concentrations.…”
Section: Introductionmentioning
confidence: 99%